Metacognitive knowledge : development, application, and improvement - Velzen, Joke van (Emerald Publishing Limited : IAP-Information Age Publishing, Inc., 2017)
An important goal in contemporary educational psychology research is adolescent students' development of higher-order thinking, which includes, among other things, that these students become competent and independent learners and problem solvers. This goal comes forth from the notion of education for life that emphasizes that students can direct their learning and problem solving of their own accord. Especially high-school students can encounter difficulties in independent learning and problem solving when they make the transition to higher education. To counter this, these students need to possess, among other things, metacognitive knowledge, which they may have insufficiently.This book offers new insights about late adolescent students' understanding of their metacognitive knowledge regarding learning and problem solving. It offers a description of a research project conducted to obtain a better understanding of the students' abilities and views with respect to what their metacognitive knowledge encompasses, and how they attempt to develop, apply, and improve this knowledge regarding learning and the solving of mathematical and first-language problems in a more effective way of their own accord. Specifically, the results of the studies of the research project enable us to understand metacognitive knowledge better, in that it provides explanations about the students' development of this knowledge across domains. This book offers further details in terms of providing evidence for theory building regarding metacognitive knowledge.